2009
DOI: 10.1093/bja/aen322
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic insults to human HepG2 cells induced by S-(+)-ketamine occurs through activation of a Bax-mitochondria-caspase protease pathway

Abstract: This study shows that S-(+)-ketamine can induce apoptotic insults to human HepG2 cells via a Bax-mitochondria-caspase protease pathway. Thus, we suggest that S-(+)-ketamine at a clinically relevant or an abused concentration may induce liver dysfunction possibly due to its toxicity to hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 34 publications
(22 reference statements)
0
60
0
2
Order By: Relevance
“…The S period is an important indication of cell proliferation, and the proportion of cells in the S period is positively associated with the ability of proliferation (15). We did not observe two typical characteristics of cells undergoing apoptosis, such as the increase of shrinking morphologies and arresting at the sub-G1 phase (16)(17)(18). This result also suggested that total flavonoids from Drynaria fortunei did not induce DPSC toxicity and apoptosis.…”
Section: Discussionmentioning
confidence: 49%
“…The S period is an important indication of cell proliferation, and the proportion of cells in the S period is positively associated with the ability of proliferation (15). We did not observe two typical characteristics of cells undergoing apoptosis, such as the increase of shrinking morphologies and arresting at the sub-G1 phase (16)(17)(18). This result also suggested that total flavonoids from Drynaria fortunei did not induce DPSC toxicity and apoptosis.…”
Section: Discussionmentioning
confidence: 49%
“…Ketamine-induced apoptosis by mitochondrial pathway has been shown in neuronal cells (Braun et al, 2010;Yon et al, 2005) as well as non-neuronal (lymphocytes and hepatic) cells (Braun et al, 2010;Lee et al, 2009). Acetyl L-carnitine appears to be involved in the restoration of mitochondrial function and/or improved use of energy from glycolysis in cultured neuroblastoma cells treated with the neurotoxicant, 1-methyl-4-phenyl tetrahydropyridine (Mazzio et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(28) Briefly, osteoblasts (2 Â 10 4 cells/well) were seeded in 96-well tissue culture plates overnight. After drug treatment, osteoblasts were cultured with new medium containing 0.5 mg/mL of MTT for a further 3 hours.…”
Section: Assay Of Cell Viabilitymentioning
confidence: 99%